Collectives and commoning in small arts - Ristić, Irena (Amfiteater (Ljubljana), 2022)
The analysis is focused on the work and actions of drag artists from Belgrade gathered in collectives, in which the practice of commoning becomes an alternative mode of social relations. Their joint actions provide an opportunity to examine the paths of radical imagination on two levels: firstly, by following the principles of collective creativity, which operate through different forms of artistic and socio-cultural production, systematically targeting the development of social imaginaries; secondly, by creating a collective, aimed at the production of sociability itself which are evolved and tested through practices. In this transposition from the level of artistic production to the level of social production, the tools of (self-)reflection can be crucial. (Self-)reflection is equally a guardian of equality and emergence. Provided that the imagination is not reduced to reactive mental representations, this becomes the drive of practice: the material manifestation of certain relations, their testing, in reality, their growing and simultaneous performing, on the path towards new forms of collectivity, and perhaps collective autonomy.
Keywords: collective creativity; commoning; drag collectives; družbeni imaginarij; kolektivna ustvarjalnost; kolektivni dragi; male umetnosti; radical imagination; radikalna domišljija; skupna raba; small arts; social imaginary